Why do the Levels of Sexual Violence Vary Across Genocides? A Comparison of the Bengali and Kurdish Genocides. Issue 2 (3rd April 2022) - Silkoset, Andrea; Skarpeteig, Margot Igland
ABSTRACT: What causes variation in the prevalence of sexual violence across genocides? We examine the conditions under which sexual violence may be used as a strategy of genocide, and the power dynamics in institutions at the state- and group-level. In order to explore the dynamics of sexual violence in genocidal campaigns we conduct a comparative study with two cases: the Bengali genocide of 1971, in which there were high levels of sexual violence, and the Kurdish genocide of 1987–1989, in which the levels of sexual violence were low. Our findings may shed light on the behaviour of armed groups and the dynamics of genocidal violence. We find that micro-dynamics and individual behaviour better explain repertoires of genocidal violence than purely structural approaches. In the two cases, there seems to be a causal link between group leaders' control and the prevalence of sexual violence. The attitude and behaviour of leaders – particularly military leaders – could immensely affect armed group's repertoire of violence. If they choose to do so, commanders are capable of building institutions to prevent rape.